TEACHER COMPETENCY IN MODEL IMPLEMENTATION TUTORIAL ON LEARNING INFORMATION AND COMMUNICATION TECHNOLOGY: STUDY AT THE AVICENNA LASEM INDONESIA INTEGRATED ISLAMIC ELEMENTARY SCHOOL - Suroyya, Camila Fatah; Tantowi, Ahmad Tantowi (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2024)
A classic problem in learning is the occurrence of learning boredom at school, which is the background for conducting this research. This research aims to analyze the competency of elementary school teachers regarding the tutorial model in information and communication technology (ICT) learning and determine the obstacles teachers have in implementing the tutorial model in ICT learning at the Avicenna Lasem Integrated Islamic Elementary School (SDIT). The research used a case study method with the research subjects being grade 3-6 teachers and one information and communication technology (ICT) teacher. Data was obtained through interviews. The research results show that conceptually, teachers understand the tutorial model in information and communication technology (ICT) learning well, but in practice, 4 out of 5 teachers studied still need to implement the tutorial model in learning. This research also reveals that teachers experience obstacles in implementing the tutorial model in information and communication technology (ICT) learning.